Memantine Effects on Verbal Memory in Fragile X-associated Tremor/Ataxia Syndrome (FXTAS): a Double-Blind Brain Potential Study - Yang, Jin-Chen (Nature Publishing Group, 2014)
Older FMR1 premutation carriers may develop fragile X-associated tremor/ataxia syndrome (FXTAS), a neurodegenerative disorder manifesting cognitive deficits that often subsequently progress to dementia. To date, there is no specific treatment available for FXTAS. Studies have demonstrated the premutation-associated overactivation of glutamatergic receptors in neurons. Memantine, a NMDA receptor antagonist approved for treatment of Alzheimer's disease, thus was tested in the first placebo-controlled, double-blind, randomized clinical trial in FXTAS. Prior event-related brain potential (ERP) studies in FXTAS found reduced N400 repetition effect, a glutamate-related electrophysiological marker of semantic priming, and verbal memory processes. This substudy of the randomized clinical trial of memantine in FXTAS sought to use the N400 repetition effect to evaluate effects of chronic memantine treatment on verbal memory. Subsequent recall and recognition memory tests for the experimental stimuli were administered to characterize verbal memory. Data from 41 patients who completed the 1-year memantine trial (21 on memantine) and also completed longitudinal ERP studies were analyzed. Results showed treatment-associated benefits on both cued-recall memory and N400 repetition effect amplitude. Importantly, improvement in cued recall was positively correlated with amplitude increase of the N400 repetition effect. The placebo group, in contrast, displayed a significant reduction of the N400 repetition effect after 1 year. These results suggest that memantine treatment may have beneficial effects on verbal memory in FXTAS. Additional studies of memantine, perhaps in combination with other therapeutic agents, appear warranted, as symptomatic treatments and neuroprotective treatments are both needed for this recently recognized neurodegenerative disorder.